Troglobitic invertebrates: improving the knowledge on the Brazilian subterranean biodiversity through an interactive multi-entry key - Parizotto, Daniele R.; Pires, Amanda Ciprandi; Mise, Kleber Makoto; Ferreira, Rodrigo Lopes (Zootaxa, 2017)
Troglobitic species are those organisms restricted to caves that frequently present unique morphological features related to these environments. In order to study its ecology, evolution and biogeography, it is first required to properly recognize them. However, especially in Brazil, the basic knowledge is still incipient, with few taxonomic studies such as identification keys for this group of organisms. In addition, since the troglobitic species belong to different taxonomic groups, the information to properly recognize them is often sparse and difficult to access. Considering this, an interactive multi entry taxonomic key available online is an interesting approach, as it makes identifications easier. This study aims to construct a multi-access interactive identification key to the troglobitic invertebrates of Brazil, using morphological characters obtained from literature and direct observations of specimens. The key was made in Lucid version 3.3, containing figures of most characters. It comprises seventy-eight species of troglobitic invertebrates that occur in Brazil, forming a matrix of 231 morphological characters and more than 200 images to support identification. The key is freely available online on lucid central (http://keys.lucidcentral.org/keys/v3/troglobitic_invertebrates/troglobitic_invertebrates.html). Since Brazilian laws regarding cave conservation has change in 2008, allowing even the destruction of caves, this multi-access identification key is step to reduce the existing taxonomic impediment and also an important tool for identification of troglobites, especially for non-specialists.